The Agricultural Innovation System of Azerbaijan: An Assessment of Institutional Linkages - Temel, Tugrul; Janssen, Willem G.; Karimov, Fuad (International Service for National Agricultural Research, 2002)
Since independence in 1991, Azerbaijan has had to contend with severe adverse developments including civil unrest, the dismantlement of inter-republic trade links, and economic blockade by its neighbors. Slow progress has been recorded with respect to the country's efforts to build institutions and establish markets with proper infrastructure, while it has received increasing attention for its rich oil reserves. Rural development in general, and agriculture in particular, have been neglected. New private-sector farmers have been oriented toward subsistence farming and have experienced declining productivity and incomes. In addition, poverty has become widespread. Promoting agricultural innovation should help the agricultural sector get out of this vicious circle. The following observations provide insights into the workings of the current agricultural innovation system (AIS), pinpoint its weaknesses, and identify areas that need to be strengthened.